Detoxification of paraoxon-ethyl by Lysiphyllum strychnifolium extracts in undifferentiated human neuroblastoma SH-SY5Y cells - Niramai Ekaratcharoenchai; Thararat Nualsanit; Aungkana Krajarng (Pharmaceutical Biology)
Context Lysiphyllum strychnifolium (Craib) A. Schmitz. (Fabaceae) is a Thai traditional medicine used to remove food and alcohol toxins from the body.Objective This study investigates the molecular mechanism of L. strychnifolium extracts against paraoxon-ethyl-induced apoptosis in SH-SY5Y cells.Materials and methods The ethanol and water extracts of leaves and stems of L. strychnifolium were prepared at various concentrations (0–100 μg/mL) and co-treated to the cells with 0.375 mM paraoxon-ethyl for 24 and 48 h. Cell viability was performed using the PrestoBlue assay. ROS and caspase activity were detected using 2′,7′-dichlorodihydrofluorecein diacetate and caspase-Glo® 3/7, 8, and 9 assay kits. Apoptotic and ER stress-related gene expression were determined by real-time PCR, and nuclear and mitochondrial morphology were observed using Hoechst 33342 and MitoTracker® Deep Red FM staining.Results The most effective concentrations of each extract against paraoxon-ethyl-induced cell death were 25 μg/mL of leaf ethanol, 12.5 μg/mL of stem ethanol, 100 μg/mL of leaf water, and 25 μg/mL of stem water extracts. The leaf ethanol extract was the most effective at detoxifying, while stem extracts were highly toxic in high doses. The detoxifying L. strychnifolium extracts against paraoxon-ethyl-induced oxidative stress decreased p53, BiP/GRP78, and CHOP gene expression and minimized caspase 9 and caspase 3, protecting cells from apoptosis. The extracts could also restore mitochondrial membrane potential and reduce the swollen globule mitochondrial shape.Discussion and conclusion These findings could potentially protect neuron cells from neurodegenerative issues due to oxidative damage, apoptosis, and other potential consequences.